Electrodynamical Analysis of the Helical Systems with Axial Symmetry - Staras, S.; Kleiza, A. (Elektronika ir Elektrotechnika, 1997)
Helical systems are applied in various electronic devices. We offer a variant of the electrodynamical method for analysis of non-homogeneous helical systems with axial symmetry. Properties of the systems are investigated and advantages are revealed.